Inter-Generational Dynamics: Understanding Changes in the Attitude of Elderly Towards Family Structures and Roles (Journal of Advances and Scholarly Researches in Allied Education, 2024)
The dissolution of the nuclear family and its replacement by the more flexible nuclear and extended family structures represents a sea shift in social organization. Despite the fact that families continue to be an invaluable resource for mental health in our modern environment, there is still a lack of family engagement in the treatment of mental illnesses. The impact of changing family structures on elder care is the focus of this research. Alterations to the country's population make a big splash on the dynamics of family structures. The elderly's current and future financial security will be affected by the fundamental shift from an extended to a nuclear family structure. The results demonstrated a steady reduction in the quality of care for the elderly and clear shifts in the composition of families. Alterations to the family dynamic impact the ways in which children provide for or assist their ageing parents. Laws should be enacted to mitigate the impact of shifting family dynamics, and families should be counselled on the significance of their main responsibility in caring for or otherwise supporting their elderly loved ones. There is no better place to find the three most significant positions in later life than inside one's own family: parent, spouse, and grandparent. So, one of the most significant factors in determining one's subjective QoL is one's family structure and the accessibility of close relatives. Additionally, the significance of intergenerational interactions inside larger family structures is growing due to present-day demographic, economic, and cultural shifts.